Transtorno do desenvolvimento da coordenação: efeito do foco de atenção em tarefa bimanual - Ferracioli, Marcela de Castro [UNESP] (2015)
Children with Developmental Coordination Disorder (DCD) have difficulties performing everyday activities. Bimanual tasks such as tying shoes and using cutlery, for example, require a different engagement of their hands and, thus, are more challenging for these children. Attention has an important role in the executive function and regulation of cognitive processes related to planning and execution of motor tasks. However, few studies have investigated whether or not the manipulation of focus of attention, during the execution of fine bimanual tasks, can be used as motor intervention strategy with children with DCD. This study investigated the effect of directing the attentional focus during execution of bimanual tasks in children with and without DCD. Twenty-eight 9-10 years old children were evaluated and composed two groups matched by age and gender based on the results of the Movement Assessment Battery for Children (MABC- 2): TDC [n=14] and typically developing (TD) [n=14]. Children participated in two experiments. In the experiment 1, the coupling of horizontal trajectories of both hands in the in-phase pattern was obtained in conditions where the focus of attention was directed, alternatively to the dominant, non-dominant hand, and self-directed condition (free). In the experiment 2, the children received an additional verbal attention cue to maintain the anti-phase pattern, as the frequency of oscillation of their hands increased. Overall, the results showed that children with DCD presented a less stable ability to couple their hands, and deficits controlling in-phase bimanual coordination patterns when the focus of attention was directed to the dominant hand. Furthermore, although the group of children with DCD displayed higher variability during the execution of the antiphase bimanual pattern, the additional cue help them to stabilize the anti-phase bimanual coordination pattern. Altogether, these findings confirm that the ...